2017
DOI: 10.1101/208314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Identification of some Indian Muscid flies (Diptera: Muscidae) based on mitochondrial gene COII

Abstract: Taxonomic identification of flies having medical and veterinary importance is often complicated due to the lookalike morphological characters. Molecular identification of five Indian muscid flies (Musca domestica, Musca sorbens, Musca crassirostris, Stomoxys calcitransand Haematobia irritans) has been attempted on the basis of mitochondrial COII gene.Sequences of 500-520 bp were analysed and found to be A+T rich. Rate of transitions was higher than transversions. The average haplotype diversity was 0.833 and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Phylogenetic analysis revealed that species belong to same family were in the same clade (Figure 4). Singh and Achint (2017) found that Musca species formed a sister clade with Haematobia irritans which supports our results. Iwasa and Ishiguro (2010) reported Haematobia and Musca as sister clade similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Phylogenetic analysis revealed that species belong to same family were in the same clade (Figure 4). Singh and Achint (2017) found that Musca species formed a sister clade with Haematobia irritans which supports our results. Iwasa and Ishiguro (2010) reported Haematobia and Musca as sister clade similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…A key to the subfamily, genus, and species is also provided by them. Molecular work on muscid flies was carried out by Malviya et al (2011Malviya et al ( , 2012Malviya et al ( , and 2015, and Singh and Achint (2017). Malviya et al (2012) conducted a study on genetic relatedness among different muscid fly species.…”
Section: State-wise Progressmentioning
confidence: 99%
“…During their study, they used the RAPD-PCR technique to show the genetic relatedness among muscid fly species. Singh and Achint (2017) studied the molecular identification of muscid flies. On the basis of the mitochondrial COII gene, five flies of the family Muscidae were identified.…”
Section: State-wise Progressmentioning
confidence: 99%